First Insights Into the Fine-Scale Movements of the Sandbar Shark, Carcharhinus plumbeus - Andrzejaczek, Samantha; Gleiss, Adrian C.; Pattiaratchi, Charitha B.; Meekan, Mark G. (Frontiers in Marine Science, 2018)
The expanding use of biologging tags in studies of shark movement provides an opportunity to compare fine-scale movement behaviours among species. In May 2017, we deployed high-resolution biologging tags on four mature female sandbar sharks Carcharhinus plumbeus at Ningaloo Reef for durations ranging between 13 and 25.5 hours. Pressure and tri-axial motion sensors within these tags enabled the calculation of dive geometry, swimming kinematics and path tortuosity at fine spatial scales (m-km) and concurrent validation of these behaviours from video recordings. Sandbar sharks oscillated through the water column at shallow dive angles, with gliding behaviour observed in the descent phase for all sharks. Continual V-shaped oscillatory movements were occasionally interspersed by U-shaped dives that predominately occurred around dusk. The bottom phase of these U-shaped dives likely occurred on the seabed, with dead-reckoning revealing a highly tortuous, circling track. By combining these fine-scale behavioural observations with existing ecological knowledge of sandbar habitat and diet, we argue that this circling behaviour is likely to be a strategy for hunting benthic prey. Comparing dive geometry and energetics with those of other sharks reveals common patterns in energetically efficient oscillatory swimming.